Cardiovascular Research New Technologies, Methods, and Applications - Pasterkamp, Gerard; de Kleijn, Dominique (Springer US : Imprint: Springer, 2006)
Cardiovascular Research: New Technologies, Methods & Applications serves as an essential reference material offering a complete overview of innovative new technologies, methods, and applications in current cardiovascular research. Cardiovascular Research: New Technologies, Methods & Applications presents a methods and applications approach to cardiovascular research written by prominent international researchers presenting commissioned summaries of cutting edge research. Key Topics: Offers a Methods and Applications approach including, Cardiovascular Methods in: -Microarrays -Proteomics -Real Time PCR -RNA Interference -Plus More! Cardiovascular Applications in: -Stems Cells and Cardiomyocytes -Stem Cells and Angiogenesis -Gene Therapy -Manufacturing the Artificial Blood Vessel -Closed Chest Robotic Surgery -RNA Interference -Plus More! Cardiovascular Research: New Technologies, Methods & Applications is essential for all cardiovascular research academics, bench scientists, and industry professionals wishing to take advantage of the latest and greatest in the continuously emerging field of cardiovascular science. About the Editors: Gerard Pasterkamp, PhD, MD is Associate Professor and Head of Experimental Cardiology Laboratory at the Heart Lung Centre Utrecht at the University Medical Center Utrecht (UMCU). Dr. Pasterkamp received his MD at Free University Amsterdam, his PhD at the medical faculty on intravascular ultrasound, and his MSc Clinical Epidemiology at the NIHES Rotterdam. Dr. Pasterkamp's many original papers and invited reviews on the topic of vascular remodeling reveal his skilled interest in arterial remodeling in atherosclerotic disease. Dominique de Kleijn, PhD is a molecular biologist at Interuniversity Cardiology Institute of the Netherlands (ICIN) and is positioned at the Laboratory of Experimental Cardiology at the UMCU. Dr. Klein earned his PhD molecular biology at the Nijmegen University at the Department of Molecular Animal Physiology, and is recognized as an expert in matrix biology and innate immunity in cardiovascular disease.